Kryzys jako skutek kryzysu funkcji pieniądza i kryzysu instytucji - Żyżyński, Jerzy (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper analyses transformation of functions of money and addition of a newone. The newest function transforms money from a right to buy goods and servicesinto the right to buy money itself.